Uniqueness of solutions for fourth-order nonlocal boundary value problems - Ding Ma; Johnny Henderson (Boundary Value Problems, 2006)
Uniqueness implies uniqueness relationships are examined among solutions of the fourth-order ordinary differential equation, y(4)=f(x,y,y′,y″,y‴), satisfying 5-point, 4-point, and 3-point nonlocal boundary conditions.